2019
DOI: 10.1038/s41419-019-1713-z
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 promotes NLRP3 inflammasome activation to mediate pyroptosis and endotoxic shock

Abstract: miR-21 is aberrantly expressed, and plays a role in various types of tumors and many other diseases. However, the mechanism of miR-21 in LPS-induced septic shock is still unclear. In this study, we investigated the mechanism of miR-21 in LPS-induced pyroptosis and septic shock. Here, we show that miR-21 deficiency inhibited NLRP3, ASC, and caspase-1 expression, as well as inflammasome activation in myeloid cells from both mice and humans. We found that the NF-κB pathway was regulated by miR-21, and that A20 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 33 publications
4
71
0
Order By: Relevance
“…miR21 is one of the most abundant microRNAs expressed during LPS challenge, cytokine (TNF, IL1β, IL6, TGFβ, GM-CSF), and lipids (PGE2 and resolvin A1) stimulation (33). miR-21 is upregulated in septic patients and mice (Figure 1 and ( These findings also corroborated with Xue et al, that showed increased miR21 KO survival during sepsis by controlling IL1-dependent inflammasome activation (40). Delivery of a miR21…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…miR21 is one of the most abundant microRNAs expressed during LPS challenge, cytokine (TNF, IL1β, IL6, TGFβ, GM-CSF), and lipids (PGE2 and resolvin A1) stimulation (33). miR-21 is upregulated in septic patients and mice (Figure 1 and ( These findings also corroborated with Xue et al, that showed increased miR21 KO survival during sepsis by controlling IL1-dependent inflammasome activation (40). Delivery of a miR21…”
Section: Discussionsupporting
confidence: 74%
“…There is no common scientific consensus about the exact mechanism of miR-21 in the induction or repression of the inflammatory program. Several manuscripts suggest miR-21 as an anti-inflammatory target (41,(73)(74)(75), while others suggested this miRNA as a crucial proinflammatory factor (36,40,76). We observed an overall decrease in IL6 and IL1b and an increase in IL10 abundance in septic miR21∆myel when compared to septic WT mice.…”
Section: Discussionmentioning
confidence: 44%
“…Indeed, functional studies in several cancer cell lines demonstrated that knockdown of miR-21 activates caspases leading to apoptotic cell death. Moreover, in vitro evidence also suggested a positive regulatory role in pyroptosis through the activation of the NLRP3 inflammasome 83 . At a molecular level, miR-21 suppresses the expression of pro-apoptotic genes, such as APAF11, PDCD4, RHOB, and FASLG ( Fig.…”
Section: Micrornas With Anti-apoptotic Functions Mir-21mentioning
confidence: 99%
“…A recent study investigated the role of this miRNA and demonstrated that miR-21 deficiency inhibited NLRP3, ASC and caspase-1 expressions. They found that knockout mice for miR-21 presented inhibited caspase-1 activation and IL-1β secretion [122]. Other studies elucidated the role of miR30e in inflammation.…”
Section: Role Of Noncoding Rna In the Regulation Of Inflammasomementioning
confidence: 99%